The role of conventional echocardiographic parameters on detecting subclinical anthracycline therapy related cardiac dysfunction—The SATRACD study - Zhang, Wanzhu; Azibani, Feriel; Libhaber, Elena; Nankabirwa, Joaniter; Okello, Emmy; Kayima, James; Ssinabulya, Isaac; Sliwa, Karen (Frontiers in Cardiovascular Medicine, 2022)
Background: Subclinical anthracycline therapy related cardiac dysfunction (ATRCD) can be detected with speckle tracking echocardiographic image(STE), which is not widely available in Uganda. We aimed to investigate the role of the two conventional echocardiographic parameters (mitral annular plane systolic excursion (MAPSE) and mitral annular peak systolic tissue Doppler velocity(S’)) on diagnosing subclinical ATRCD. Method and results: 207 cancer patients who underwent anthracycline based chemotherapy were recruited at baseline and followed up until 6 months after ending anthracycline therapy. Comprehensive echocardiographic data were collected at each visit. Global longitudinal strain (GLS) by STE was used as the gold standard diagnostic test to define the case of subclinical ATRCD. Data of the 200 patients who had no evidence of clinical ATRCD were analyzed. One hundred and seventy-two (86.0%) were female, with a median age of 42 years and 47(23.5%) patients were diagnosed with subclinical ATRCD at the end of anthracycline therapy by GLS criteria. The area under the curve (AUC), cutoff point, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of reduction of MAPSE (ΔMAPSE) were 0.6736 (95% CI: 0.5885, 0.7587), ≥2mm, 74.5% (95% CI: 59.7%, 86.1%), 54.9% (95% CI: 46.7%, 63.0%), 33.7% (95% CI: 24.7%, 43.6%) and 87.5% (95% CI: 79.2%, 93.4%). The AUC, cutoff point, sensitivity, specificity, PPV and NPV of reduction of S’ (ΔS’) were 0.6018 (95% CI: 0.5084, 0.6953), ≥0.5cm/s, 61.7% (95% CI: 46.4%,75.5%), 52.7% (95% CI: 44.4%, 60.9%), 29.0% (95% CI: 20.4%, 38.9%) and 76.1% (95% CI:72.4%, 88.6%). When ΔMAPSE and ΔS’ are used as parallel test, the net sensitivity and specificity is 89.4% and 28.8% respectively, the net PPV and NPV is 27.8% and 90.0% respectively. Conclusion: The ΔMAPSE and ΔS’ showed fairly good accuracy, sensitivity and negative predictive value to detect subclinical ATRCD in Ugandan cancer patients. These conventional echocardiographic parameters may serve as screening tools for detecting subclinical ATRCD in resource limited settings.